Influence of heat treatment on H2S gas sensing features of NiO thin films deposited via thermal evaporation technique. (February 2023) - Dastan, Davoud; shan, Ke; Jafari, Azadeh; Marszalek, Tomasz; Mohammed, Mustafa K.A.; Tao, Lin; Shi, Zhicheng; Chen, Yingxin; Yin, Xi-Tao; Alharbi, Najlaa D.; Gity, Farzan; Asgary, Somayeh; et al.
Abstract: In this study, NiO thin films are prepared on Ni foil using thermal evaporation method and the effect of deposition conditions on structural, morphological and H2 S gas sensing properties of NiO thin films is investigated. Structural analysis of the NiO films are conducted by means of X-ray diffraction (XRD), and the films are found to have the FCC phase with preferred (111) and (200) Bragg reflections. Based on XRD and scanning electron microscopy results, it is shown that the crystallite size and the size of homogeneous nanoclusters on the surface of the films increase after increasing oxidation temperature. Also, the EDS patterns of NiO films demonstrate a rise in the intensity of O peak upon increasing the oxidation temperature due to the enhancement of oxygen in the NiO films. The Raman spectrum of NiO thin films several bands correspond to Ni–O vibrations. The obtained gas sensing results demonstrate the sensing response to 20 ppm of hydrogen sulfide at 700 °C. Upon increasing the amount of hydrogen sulfide gas to more than 20 ppm, the fabricated sensors show no significant change in their response, indicating that no additional active sites were exist to interplay with hydrogen sulfide molecules for the higher concentration of hydrogen sulfide. The response of the sensors, recorded 10 s after H2 S gas exposure, depended on the deposition temperature. The current study shows that NiO thin films-based sensors prepared by a simple thermal evaporation method are potentially useful for the detection of H2 S gas.